THRIFTING CONSUMER PURCHASE DECISION FACTORS IN INDONESIA: SYSTEMATIC LITERATURE REVIEW (SLR) - Rahayuningtyas, Dwi Besti; Budi Santoso; Zakiyyah, Amalina Maryam (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research aims to analyze the factors that influence the decision to purchase second-hand clothing (thrifting) through the Systematic Literature Review (SLR) approach that focuses on psychological, social, economic, and environmental aspects to provide a more holistic understanding of the thrifting phenomenon in Indonesia. Method: This research was conducted using the SLR approach based on the guidelines of Kitchenham and Charters (2007). A total of 20 journals published in the last 5 years with a focus on second-hand clothing purchasing decisions were selected through an online searching on Google Scholar. The research involved the stages of planning, implementation, and reporting, with article selection based on inclusion and exclusion criteria. Results: The results showed that second-hand clothing purchasing decisions were influenced by environmental awareness, social media trends, lifestyle orientation, and product quality and affordable price factors. Social media has become an important platform in driving consumer interest in thrifting, while sustainability aspects are increasingly becoming a major consideration in purchasing. Novelty: The novelty of this research lies in the application of the SLR approach to explore second-hand clothing purchasing decisions with a primary focus on the Indonesian context. This research provides theoretical contributions on the integration of psychological, social, and environmental factors, while also offering strategic insights for thrifting entrepreneurs in Indonesia to develop evidence-based marketing strategies. This research is expected to be a primary reference in the literature on sustainable consumerism.